PENELITIAN MENGENAI PENINGKATAN KEKUATAN AWAL BETON PADA SELF COMPACTING CONCRETE - Handoko Sugiharto; Tedy Gunawan; Yusuf Muntu (Civil Engineering Dimension, 2006)
High Early Strength Self Compacting Concrete, a new phenomenon in the world of concrete technology, offers advantages such as high workability, high durability and high early strength characteristic that can well be applied especially in the pre-cast concrete industry. In this study the properties of High Early Strength Self Compacting Concrete is achieved by the use of admixture (hyper plasticizer) Glenium Ace-80 and Silica Fume Rheomac SF 100 as filler. The water-binder ratio is kept in the low level. The workability conditions are tested using workability test like Slump Cone, V-Funnel, and L-Shaped Box. To test the High Early Strength characteristic compression tests are carried out on 1, 3, 7, 14 and 28 days of concrete age. The tests were focused on the age 1 and 28 days. The test result shows that the use of 2.5 % Glenium Ace-80 and 2 % Silica Fume can fulfill both workability and high early strength requirement of Self Compacting Concrete High Early Strength by keeping the value of water-binder ratio in the low level. Abstract in Bahasa Indonesia : High Early Strength Self Compacting Concrete (HESSCC), sebuah fenomena baru dalam dunia teknologi beton, memiliki keunggulan workability, durabilitas dan kekuatan awal yang tinggi, sehingga dapat diaplikasikan dengan baik khususnya pada dunia usaha pre-cast concrete. Dalam penelitian ini digunakan admixture (hyperplasticizer) Glenium Aceâ80 dan filler Silica Fume Rheomac SF 100 dengan water-binder ratio rendah. Pengujian workability dilakukan dengan menggunakan alat Slump Cone, V-Funnel dan L-Shaped Box, sedangkan tes kuat tekan beton dilakukan pada umur 1, 3, 7, 14, 28 hari. Tes kuat tekan ini diutamakan untuk umur 1 hari untuk kuat tekan awal dan 28 hari untuk kuat tekan akhir dari beton. Hasil penelitian menunjukkan penggunaan Silica Fume sebesar 2 % dan Glenium Ace-80 sebesar 2.5 % sudah mampu mencapai kriteria self compactible sekaligus kuat tekan awal (High Early Strength) yang baik pula, karena nilai water-binder ratio tetap dijaga pada nilai yang rendah